Testing Site Amplification Curves in Hybrid Broadband Ground Motion Simulations of M6.0, 24 August 2016 Amatrice Earthquake, Italy - Pischiutta, Marta; Akinci, Aybige; Felicetta, Chiara; Pacor, Francesca; Morasca, Paola (Frontiers in Earth Science, 2022)
This research focuses on predicting and assessing earthquake impact due to future scenarios regarding the ground motion seismic hazard by accounting mainly for site effect in the Central Apennines. To this end, we produced synthetic broad-band seismograms by adopting a hybrid simulation technique for the Mw6.0 Amatrice earthquake, Central Italy, on 24 August 2016, accounting for site condition by means of amplification curves, computed with different approaches. Simulations were validated by comparing with data recorded at 57 strong-motion stations, the majority installed in urban areas. This station sample was selected among stations recording Amatrice earthquake within an epicentral distance of 150 km and potentially prone to experience site amplification effects because of lying in particular site conditions (sedimentary basins, topographic irregularities, fault zones). The evaluation of amplification curves best suited to describe local effects is of great importance because many towns and villages in central Italy are built in very different geomorphological conditions, from valleys and sedimentary basins to topographies. In order to well reproduce observed ground motions, we accounted for the site amplification effect by testing various generic and empirical amplification curves such as Horizontal-to-Vertical Spectral Ratios (calculated from Fourier spectra using both earthquakes, HVSR, and ambient noise, HVNSR, recordings), and those derived from the Generalized Inversion Technique (GIT). The site amplifications emanated from GIT improve the match between observed and simulated data, especially in the case of stations installed in sedimentary basins, where the empirical amplification curve effectively reproduces spectral peaks. On the contrary, the worst performances are for the spectral ratios between components, even compared to the generic site amplification, although the latter ignores the strong bedrock/soil seismic impedance contrasts. At sites on topography, we did not observe any systematic behavior, the use of empirical curves ameliorating the fit only at a small percentage of cases. These results may provide a valuable framework for developing ground-motion models for earthquake seismic hazard assessment and risk mitigation, especially in urban areas located in the seismically active central Italy region.